Amitriptyline enhances the central component of physiological tremor. Issue 1 (1st January 2001) - Raethjen, J; Lemke, M R; Lindemann, M; Wenzelburger, R; Krack, P; Deuschl, G
Abstract : OBJECTIVES: Postural tremor is a regularly encountered side effect of amitriptyline which can be strong enough to cause discontinuation of therapy. The aim was to characterise amitriptyline induced tremor and to assess if the central or reflex component of physiological tremor was modulated by this drug. METHODS: The postural hand tremor was measured in 15 patients on a clinical rating scale, by power spectral analysis of accelerometer, forearm flexor, and extensor EMG before and after the beginning of amitriptyline treatment for major depression or chronic pain syndrome. A coherence analysis between flexor and extensor muscles on the same side was performed. RESULTS: There was a clinically visible increase in postural tremor in a third of these patients. The tremor amplitude measured by accelerometer total power increased in every patient under amitriptyline. The EMG synchronisation as reflected by significant peaks in the flexor or extensor spectrum generally occurring at higher frequencies (8–18 Hz) than the accelerometric tremor frequencies (6–11 Hz) did not change. The number of patients with a significant flexor-extensor coherence in the 7–15 Hz range increased significantly under amitriptyline, the frequency bands of significant coherence corresponded with the EMG frequencies, and both were independent of changes to the hand's resonant frequency by added inertia. CONCLUSIONS: An enhancement of postural tremor under amitriptyline is a common phenomenon although not always clinically apparent. The increase in EMG-EMG coherence indicates an increased common central drive to the motor units as its frequency is not influenced by peripheral resonance or reflex mechanisms. This is the first account of a drug induced enhancement of the central component of physiological tremor.